Outbreak of human malaria caused by Plasmodium simium in the Atlantic Forest in Rio de Janeiro: a molecular epidemiological investigation - Dr Patrícia Brasil, MD; Mariano Gustavo Zalis, PhD; Anielle de Pina-Costa, PhD; Andre Machado Siqueira, MD; Cesare Bianco Júnior, BSc; Sidnei Silva, MSc; André Luiz Lisboa Areas, MSc; Prof Marcelo Pelajo-Machado, MD; Denise Anete Madureira de Alvarenga, MSc; Ana Carolina Faria da Silva Santelli, MD; Hermano Gomes Albuquerque, MSc; Pedro Cravo, PhD; et al. (Elsevier, 2017)
Background: Malaria was eliminated from southern and southeastern Brazil over 50 years ago. However, an increasing number of autochthonous episodes attributed to Plasmodium vivax have recently been reported from the Atlantic Forest region of Rio de Janeiro state. As the P vivax-like non-human primate malaria parasite species Plasmodium simium is locally enzootic, we performed a molecular epidemiological investigation to determine whether zoonotic malaria transmission is occurring. Methods: We examined blood samples from patients presenting with signs or symptoms suggestive of malaria as well as from local howler monkeys by microscopy and PCR. Samples were included from individuals if they had a history of travel to or resided in areas within the Rio de Janeiro Atlantic Forest, but not if they had malaria prophylaxis, blood transfusion or tissue or organ transplantation, or had travelled to known malaria endemic areas in the preceding year. Additionally, we developed a molecular assay based on sequencing of the parasite mitochondrial genome to distinguish between P vivax and P simium, and applied this assay to 33 cases from outbreaks that occurred in 2015, and 2016. Findings: A total of 49 autochthonous malaria cases were reported in 2015-16. Most patients were male, with a mean age of 44 years (SD 14·6), and 82% lived in urban areas of Rio de Janeiro state and had visited the Atlantic Forest for leisure or work-related activities. 33 cases were used for mitochondrial DNA sequencing. The assay was successfully performed for 28 samples, and all were shown to be P simium, indicative of zoonotic transmission of this species to human beings in this region. Sequencing of the whole mitochondrial genome of three of these cases showed that P simium is most closely related to P vivax parasites from South America. The malaria outbreaks in this region were caused by P simium, previously considered to be a monkey-specific malaria parasite, related to but distinct from P vivax, and which has never conclusively been shown to infect people before. Interpretation: This unequivocal demonstration of zoonotic transmission, 50 years after the only previous report of P simium in people, leads to the possibility that this parasite has always infected people in this region, but that it has been consistently misdiagnosed as P vivax because of an absence of molecular typing techniques. Thorough screening of local non-human primates and mosquitoes (Anopheline) is required to evaluate the extent of this newly recognised zoonotic threat to public health and malaria elimination in Brazil. Funding: Fundação Carlos Chagas Filho de Amparo à Pesquisa do Estado de Rio de Janeiro, The Brazilian National Council for Scientific and Technological Development (CNPq), JSPS Grant-in-Aid for scientific research, Secretary for Health Surveillance of the Brazilian Ministry of Health, Global Fund, Fundaçao de amparo à pesquisa do estado de Minas Gerais (Fapemig), and PRONEX Program of the CNPq.